THE EFFECT OF INVESTMENT ON INDONESIA'S ECONOMIC GROWTH WITH GOVERNMENT EXPENDITURES AS A MODERATING VARIABLE - Manullang, Rizal R.; Sirait, Evi; Syofya, Heppi; Azkia, Muhamad; Harsono, Iwan (ITB AAS Indonesia Surakarta, 2024)
Abstract This research is quantitative research with an explanatory approach which uses a number of previous studies such as the five mentioned above as references for finding new variations in the research being carried out. The data used in this research is secondary data that researchers obtained from the annual reports of the Central Statistics Agency from 2004 to 20024 for 20 years. The researchers analyzed these data using the Samrt PLS 4.0 analysis tool with several stages, namely validity testing, reliability testing, and path coefficients which determine whether the hypotheses used in this research can be accepted or not. The result in this article show that the investment variable can have a positive relationship and a significant influence on economic growth because the P-Values have a positive value and are below the 0.05 significance level, namely 0.013.. This means that the more stable, large and well-utilized Indonesia is, the better the economic growth will be. In contrast to the research results above, in the second row of the third table the flow coefficients in this research show different results if the Government Expenditure variable does not have a positive and significant influence on Economic Growth because the P-Values are not below the 0.05 significance level. This means that the greater the Government Expenditure, it does not affect Economic Growth at all because there are still many other factors and variables that need to be considered, such as Good Corporate Governance variables, Education variables, HDI, and so on which make sense in influencing Economic Growth. Based on the explanation above, it can be concluded that the first hypothesis in this research can be accepted and the second hypothesis in this research cannot be accepted. Keywords: Investment, Economic Growth, Government Expenditures